Sensitization to Alternaria in children in Samara - К. S. Mazokha; M. V. Manzhos; N. N. Zhukova; E. V. Makova; T. V. Moiseeva (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
.